PENGARUH CORPORATE GOVERNANCE DAN KUALITAS AUDIT TERHADAP TAX AVOIDANCE - Diandra, Prita Karina; Ariani, Yovita (Balance Vocation Accounting Journal, 2023)
This research aims to determine the influence of institutional ownership, audit quality, audit committee and independent board of commissioners on tax avoidance. The research population used is manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The total sample data used was 94 samples using purposive sampling technique, and the method used was multiple linear regression. The results of this research show that institutional ownership, audit quality and audit committees have no effect on tax avoidance, while the independent board of commissioners has a significant effect on tax avoidance